Comparison of antibiotics included in national essential medicines lists of 138 countries using the WHO Access, Watch, Reserve (AWaRe) classification: a cross-sectional study. Issue 10 (October 2021) - Adekoya, Itunuoluwa; Maraj, Darshanand; Steiner, Liane; Yaphe, Hannah; Moja, Lorenzo; Magrini, Nicola; Cooke, Graham; Loeb, Mark; Persaud, Nav
Summary: Background: The WHO Model List of Essential Medicines classified antibiotics into Access, Watch, and Reserve (AWaRe) categories for the treatment of 31 priority bacterial infections as a tool to facilitate antibiotic stewardship and optimal use. We compared the listing of antibiotics on national essential medicines lists (NEMLs) to those in the 2019 WHO Model List and the AWaRe classification database to determine the degree to which NEMLs are in alignment with the AWaRe classification framework recommended by WHO. Methods: In this cross-sectional study, we obtained up-to-date (data after 2017) NEMLs from our Global Essential Medicines (GEM) database, WHO online resources, and individual countries' websites. From the 2019 WHO Model List we extracted, as a reference standard, a list of 37 antibiotics (44 unique antibiotics after accounting for combination drugs or therapeutically equivalent drugs as specified by WHO) that were considered essential in treating 31 of the most common and severe clinical infectious syndromes (priority infections). From the WHO AWaRe Classification Database, which contains commonly used antibiotics globally, we extracted a list of 122 AWaRe antibiotics listed by at least one country in the GEM database. We then assessed individual countries' NEMLs for listing of the 44 essential and 122 commonly used antibiotics, overall and according to AWaRe classification group. We also evaluated and summarised the listing of both first-choice and second-choice treatments for the 31 priority infections. A total coverage score was calculated for each country by assigning a treatment score of 0–3 for each priority infection on the basis of whether first-choice and second-choice treatments, according to the 2019 WHO Model List, were included in the country's NEML. Coverage scores were then compared against the score of the 2019 WHO Model List and across World Bank income groups and WHO regions. Findings: As of July 7, 2020, we had up-to-date NEMLs for 138 countries. Of the 44 unique essential antibiotics, 24 were Access, 15 were Watch, and five were Reserve. The median number of total essential antibiotics listed across the 138 NEMLs was 26 (IQR 21–32). 102 (74%) countries listed at least 22 (50%) of the 44 essential antibiotics. The median number of total AWaRe antibiotics listed by the 138 countries was 35 (IQR 29–46), of Access antibiotics was 18 (16–21), of Watch antibiotics was 16 (11–22), and of Reserve antibiotics was one (0–2). 56 (41%) countries did not list any essential Reserve antibiotics. 131 (95%) countries had coverage scores of at least 60, equivalent to at least 75% of the score of the 2019 WHO Model List, which was 80. Nine (7%) countries listed fewer than 12 of 24 essential Access antibiotics, and seven (5%) did not list sufficient first-choice and second-choice treatments for priority infections (ie, they had coverage scores lower than 60). Of the 31 priority infections, acute neonatal meningitis and high-risk febrile neutropenia did not have enough listed treatments, with 82 (59%) countries listing no treatment for acute neonatal meningitis and 84 (61%) countries listing only a first-choice treatment, only a second-choice treatment, or no treatment for high-risk febrile neutropenia. Coverage scores differed between countries on the basis of World Bank income groups (p=0·025). Interpretation: Our findings highlight potential changes to the antibiotics included in NEMLs that would increase adherence to international guidance aimed at effectively treating infectious diseases while addressing antimicrobial resistance. Funding: Canadian Institutes of Health Research and Ontario Strategy for Patient Oriented Research Support Unit.